Humans, more humane in difficults times - Boluarte Drago, Analyda (2021)
Within the current health emergency that we are experiencing globally and nationally due to COVID-19, we have witnessed various human manifestations, which in other circumstances would go unnoticed. It is really in extreme situations where the greatness and the lowest of pettiness come to light. This article reflects on the crisis in which we find ourselves as a result of COVID-19. It validates, in the first section, whether adversity can be an opportunity. In the second section, it tries to enlighten the human being so that it can be considered whether we have the necessary conditions to self-determine our way towards personal improvement despite the harsh environment. The last section highlights the primary role that education has in the task of gaining humanity and personal excellence.